2006
DOI: 10.1093/aje/kwj364
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer and Exposure to Water Disinfection By-Products through Ingestion, Bathing, Showering, and Swimming in Pools

Abstract: Bladder cancer has been associated with exposure to chlorination by-products in drinking water, and experimental evidence suggests that exposure also occurs through inhalation and dermal absorption. The authors examined whether bladder cancer risk was associated with exposure to trihalomethanes (THMs) through ingestion of water and through inhalation and dermal absorption during showering, bathing, and swimming in pools. Lifetime personal information on water consumption and water-related habits was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
295
4
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(321 citation statements)
references
References 19 publications
7
295
4
6
Order By: Relevance
“…2,3 Experimental evidence has suggested that the mechanisms behind DBP carcinogenicity may partially be explained by epigenetic alterations that result from chronic cytotoxicity mediated by a mixture of oxidative metabolites release, reductive free radicals, and cell integrity disruption. 5,32 For non-genotoxic compounds, cycles of mitotic regeneration in response to cytotoxicity may produce cumulative epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Experimental evidence has suggested that the mechanisms behind DBP carcinogenicity may partially be explained by epigenetic alterations that result from chronic cytotoxicity mediated by a mixture of oxidative metabolites release, reductive free radicals, and cell integrity disruption. 5,32 For non-genotoxic compounds, cycles of mitotic regeneration in response to cytotoxicity may produce cumulative epigenetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…53 The pipeline used (adapted from RnBeads) 54 included the following steps: (1) loading raw intensity data (idat); 55 (2) prefiltering (removal of SNP-enriched probes, greedycut algorithm removal of unreliable measurements, and removal of predefined blacklisted probes-all crossreactive probes and polymorphisms as reported by Chen et al 51 ); (3) normalization (methylumi-noob for background correction 56 and dasen normalization 57 ); (4) quality control (detection and exclusion of technical failures during bisulfite conversion, hybridization, extension and staining, detection of potential sample mixups using the default 65 SNPs included in the array); (5) postfiltering (removal of non CpG probes, removal of sex chromosomes); (6) negative control batch effect correction 58 and surrogate variable analysis-sva multidimensional reduction adjusting for residual confounding; (7) visualization of the general unadjusted methylation profile. Once data were clean, the downstream data analysis was performed using b values.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent modelling of THM uptake suggested that swimming may lead to the highest levels in the blood (Whitaker et al 2003). Uptake of DBPs through showering, bathing and swimming was associated with an increased risk of bladder cancer in a recent Spanish epidemiology study (Villanueva et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Several epidemiological studies suggest a link between consumption of chlorinated drinking water and reproductive and developmental outcomes, such as increased spontaneous abortions and intrauterine growth retardation [10][11][12][13][14], and bladder and gastrointestinal tract cancers [15][16][17][18][19][20][21]. At present, which by-products in chlorinated drinking water could be responsible for increasing cancer risk in human beings is not well established, because the potential synergistic interactions of chlorinated by-products and their role in the molecular mechanisms of carcinogenesis are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%